Caracterização bioquímica e funcional da ação da peptidase de Thermomucor indicae-seudaticae N31 sobre a caseína - Geraldes, Fernanda Martucci [UNESP] (2013)
Peptidase enzymes are responsible for catalyze the cleavage of peptide bonds of other proteins. These enzymes present great importance, therefore, are used in several industrial segments, since the food industry even in the processing of leather and formulations of medicinal products. One major application of peptidases is in the dairy industry for cheese production, which initially involves clotting of milk caseins by the action of coagulant proteolytic enzymes being rennin the main one. Microbial rennet-like milk-clotting enzymes are aspartic proteinases that catalyze milk coagulation, substituting calf rennet. In previous study it was isolated a thermophilic fungus Thermomucor indicae-seudaticae N31 that produced on Solid State Fermentation (SSF), a peptidase with capacity to hydrolyses the k-casein of milk and produce good quality curd. However its functional characterization and specificity of action is not clear yet. Thus, in this study we continued the investigation of structure and action of this enzyme coagulant. Was carried out the monitoring of enzymatic hydrolysis of casein by high performance liquid chromatography-reverse phase, was analyzed the specificity of primary peptidase using substrate of fluorescence resonance energy transfer (FRET) peptide series Abz-LSFMAIQ-EDDnp and determined the primary sequence of the protein by mass spectrometry. Monitoring the enzymatic hydrolysis of casein by high performance liquid chromatography-reverse phase showed that the crude extract Thermomucor indicae-seudaticae N31 shows high similarity with commercial enzymes brands Bela-Vista and Chr-Hansen obtained from fungi Rhizomucor miehei and Aspergillus niger, respectively. The analysis of primary peptidase specificity demonstrated high specificity and affinity for the synthetic substrate. The determination of the cleavage site showed 46% hydrolysis of the bond between the amino acids phenylalanine and methionine and 54% between alanine ...